Modeling shear behavior of rock joints: A focus on interaction of influencing parameters. (October 2020) - Babanouri, Nima; Asadizadeh, Mostafa; Hasan-Alizade, Zahra
Abstract: One of the principal issues in the design of surface and underground structures on/in rock is the shear behavior of rock discontinuities that irreparable damages are caused when neglecting it. Several parameters are involved in the shear behavior of rock discontinuities which can interact with each other. The purpose of this study is to model the shear behavior of rock joints with regard to the individual impact of the influencing parameters and their interaction. To do so, a number of direct shear tests was performed where the values of independent parameters including the compressive strength ( σ c ), normal stress ( σ n ), modulus of elasticity ( E ), joint roughness coefficient ( JRC ) and basic friction angle ( ϕ b ) were varied. Then, the response surface methodology (RSM) was used to incorporate the individual influence and interaction of the parameters into constitutive relationships for the peak shear strength, peak shear displacement, and dilation angle. For the shear strength, the most significant interaction was found to be between E and ϕ b, for the peak shear displacement between JRC and E, and for the dilation angle between σ c and E . The results show that the proposed model performs better in estimating the shear behavior characteristics than the model obtained from the nonlinear regression and the Barton-Bandis model. Therefore, the application of RSM is a winning approach for modeling the rock shear behavior which is capable of modeling the most complex interactions and provides a reliable performance.